2004
DOI: 10.1038/ng1470
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genome degradation in Paratyphi A and Typhi, human-restricted serovars of Salmonella enterica that cause typhoid

Abstract: Salmonella enterica serovars often have a broad host range, and some cause both gastrointestinal and systemic disease. But the serovars Paratyphi A and Typhi are restricted to humans and cause only systemic disease. It has been estimated that Typhi arose in the last few thousand years. The sequence and microarray analysis of the Paratyphi A genome indicates that it is similar to the Typhi genome but suggests that it has a more recent evolutionary origin. Both genomes have independently accumulated many pseudog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
373
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(402 citation statements)
references
References 46 publications
25
373
1
3
Order By: Relevance
“…This is in line with other genomes of enteric bacteria sequenced so far which feature a single chromosome with 4.3-5.0 Mb in length (7)(8)(9)(10). A comparison of S. typhi isolates from around the world indicate that they are highly related and that they emerged from a single point of origin approximately 30,000 to 50,000 years ago (11).…”
Section: Molecular and Biologic Features Of Salmonella Typhisupporting
confidence: 84%
See 1 more Smart Citation
“…This is in line with other genomes of enteric bacteria sequenced so far which feature a single chromosome with 4.3-5.0 Mb in length (7)(8)(9)(10). A comparison of S. typhi isolates from around the world indicate that they are highly related and that they emerged from a single point of origin approximately 30,000 to 50,000 years ago (11).…”
Section: Molecular and Biologic Features Of Salmonella Typhisupporting
confidence: 84%
“…Unlike most other serovars, Salmonella typhi expresses the Vi polysaccharide capsule, an important virulent factor. However, its presence only increases the infectivity of Salmonella typhi and the severity of the disease but is not essential for infection since it has been shown that Vi negative mutants are able to cause a typhoid-like illness in human volunteers (7,31). Supporting this view is the fact that there have been reports of outbreaks of typhoid fever caused by Vi-negative Salmonella typhi (32).…”
Section: Molecular and Biologic Features Of Salmonella Typhimentioning
confidence: 99%
“…S. Typhi and S. Paratyphi A are more closely related at the DNA level than other Salmonella serovars, as indicated by whole genome sequence comparisons (McClelland et al, 2004). The genomic sequences of S. Typhi strain CT18 (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…For pathogenic Salmonella spp., genome sequencing efforts have identified over 15 distinct fimbrial types (Salmonella enterica serovars Typhimurium [42], Typhi [44], and Paratyphi [41]). Pioneering work by Baumler et al (5) and subsequent genomic comparisons (14,45,61) revealed that most fimbrial operons have a scattered distribution throughout the salmonellae.…”
mentioning
confidence: 99%